Prevalence of Dehydration in Egyptian Primary School Children and its Impact on their Cognitive Performance - Mohamed Salah Abugabal, Wafaa Ibrahim; Shabaan, Sanaa Youssef; Showman, Ahmed; Youssef, Azza Mohammed; El-Gendy, Yasmin Gamal (International Journal of Child Health and Nutrition, 2024)
Background: The majority of children globally, over 75%, do not meet the water intake recommendations set by the Institute of Medicine (IOM). More than 80% of children in Europe drink less water than the European Food Safety Authority (EFSA) guidelines suggest. Hydration has been linked to cognitive performance in school-aged children living in hot climates, affecting visual attention, memory span, semantic flexibility, and arithmetic skills. This study aimed to assess the hydration status of Egyptian primary school children and its relation to cognitive function. Results: The study included 200 children aged 9-13 years from various schools in Cairo. A questionnaire and a "fluids and liquid food" diary were used to collect data on beverage consumption. Hydration status was determined using a self-reported urine color scale. Only 54 children (27%) had adequate knowledge of proper water intake, while 146 children (73%) did not. According to EFSA guidelines, 166 children (83%) reported low water intake, and 34 children (17%) had adequate intake. Dehydration was found in 118 children (59%), with 34 children (17%) severely dehydrated. There was a significant positive correlation between total fluid intake and cognitive functions, including visual attention, memory, search, and visuomotor performance (p<0.001). International school students had higher water intake during school hours and overall daily intake than students from local public schools. The most consumed fluids after water were sugar-sweetened beverages and fruit juices. Conclusions: The study highlights a significant gap in knowledge and practice regarding adequate water intake among Egyptian primary school children. A considerable number of children (83%) consumed inadequate daily fluid intake, with only 17% meeting EFSA guidelines. A significant negative correlation between total fluid intake and urine color indicates hydration status. The positive correlation between hydration and cognitive function underscores the importance of promoting proper hydration to enhance cognitive performance. Educational interventions are needed to improve water intake habits among children.